Prognostic Value of Inflammatory Markers in Colorectal Cancer Patients - CAKCAK, Ibrahim Ethem; Aytin, Yusuf Emre; KAYABAS, Merve Yaren; Ermeydan, Meltem; CANSIZ, Sıla Nur (International Journal of Innovative Research in Medical Science, 2022)
Objective: The aim of this study is to show whether the parameters used as inflammatory markers have a predictive value for evaluating colon cancer staging. Material and Method: In this retrospective study, patients who appealed to XXX University Medicine Faculty, Department of General Surgery, and had surgical treatment for colorectal cancer between January 2018 and March 2021 were evaluated. The neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and lymphocyte/monocyte ratio (LMR), prognostic nutritional index (PNI), systemic inflammation index (SII) Glasgow prognostic score (GPS) and systemic inflammatory response index (SIRI) were calculated with laboratory results. Mann-Whitney U test was used for the variations which are contrary to the normal distribution range in the comparison of two groups. The relations between qualitative variations were studied by the Kruskal Wallis test, Pearson Chi-Square test and Fisher's Exact test. Significant value was determined as 0.05 for all statistical analyses. Results: A total of 415 patients, 166 (40%) male and 249 (60% female), were included in the study. The mean age was 63.9 ±11.7 years. It was observed that GPS and SII values increased significantly with the stage (p=0.008), while the PNI value decreased significantly as the stage increased (p=0.002). There was no correlation between the other parameters and the stage. Conclusion: Although it was shown in our study that there may be a relationship between some inflammatory parameters and colon cancer staging, it is clear that there is a need for multicenter, prospective studies with larger numbers of patients.